Pre-operative interventions (non-surgical and non-pharmacological) for patients with hip or knee osteoarthritis awaiting joint replacement surgery – a systematic review and meta-analysis - Wallis, Jason A.; Taylor, Nicholas F. (Osteoarthritis and cartilage, 2011)
To determine if pre-operative interventions for hip and knee osteoarthritis provide benefit before and after joint replacement. Systematic review with meta-analysis of randomised controlled trials (RCTs) of pre-operative interventions for people with hip or knee osteoarthritis awaiting joint replacement surgery. Standardised mean differences (SMD) were calculated for pain, musculoskeletal impairment, activity limitation, quality of life, and health service utilisation (length of stay and discharge destination). The GRADE approach was used to determine the quality of the evidence. Twenty-three RCTs involving 1461 participants awaiting hip or knee replacement surgery were identified. Meta-analysis provided moderate quality evidence that pre-operative exercise interventions for knee osteoarthritis reduced pain prior to knee replacement surgery (SMD (95% CI) = 0.43 [0.13, 0.73]). None of the other meta-analyses investigating pre-operative interventions for knee osteoarthritis demonstrated any effect. Meta-analyses provided low to moderate quality evidence that exercise interventions for hip osteoarthritis reduced pain (SMD (95% CI) = 0.52 [0.04, 1.01]) and improved activity (SMD (95% CI) = 0.47 [0.11, 0.83]) prior to hip replacement surgery. Meta-analyses provided low quality evidence that exercise with education programs improved activity after hip replacement with reduced time to reach functional milestones during hospital stay (e.g., SMD (95% CI) = 0.50 [0.10, 0.90] for first day walking). Low to moderate evidence from mostly small RCTs demonstrated that pre-operative interventions, particularly exercise, reduce pain for patients with hip and knee osteoarthritis prior to joint replacement, and exercise with education programs may improve activity after hip replacement.